DISPERSION OF REACTION RATE OF IMMOBILIZED ENZYMES DURING ENZYME INHIBITOR CONCURRENT BINDING (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
In this paper the dispersion of reaction rate of immobilized enzymes during enzyme inhibitor concurrent binding was calculated. It is shown that in substrate small concentration the dispersion grows linearly with increasing of that concentration, and when the number of substrates is huge the dispersion is decreasing. It’s also shown that the presence of inhibitor doesn’t affect on maximal dispersion value in comparison with the case when there is no inhibitors. Inhibitor moves the maximum coordinate to the side of big concentration.
Keywords: immobilized enzymes; dispersion; reaction rate; inhibitor